Dampak Implementasi PP Nomor 46 Tahun 2013 ditinjau dari Perilaku Kepatuhan Pajak - Prihantari, Gusti Ayu Putu Eka Dewi; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 12 No 2 (2015), 2016)
This study aims to determine the impact of the implementation of Government Regulation Number 46 Year 2013 in terms of tax compliance behavior in SMEs in Denpasar viewed from the aspect of justice , aspects of ability to pay , and the tax burden . The number of samplesin this study were 57 UMKM . Data analysis technique esused in this research is descriptive technique . Based on the analysis found that the impact of the implementation of Government Regulation No.46 of 2013 in terms of aspects of the ability to pay ar e included in the category of fair taxation . Meanwhile , in equity aspects and tax burden unfairly categorized as final income tax of 1 % is considered unprofitable and taxation according turnover considered harmful because of profitability and turnover of different businesses , and tend to be detrimental to SMEs that have taxable income of lesst han 8 %.
Keywords: government regulation, Ability To Pay Aspect, Aspect Justice Taxation, Tax Burden.